Strategi Manajemen Program Literasi Dalam Meningkatkan Minat Baca Siswa Di MTS Negeri 3 Kota Surabaya - Hotimah, Husnul; Mardiyah, Mardiyah; Thohir, Muhammad (JURNAL MANAJEMEN PENDIDIKAN, 2025)
LITERACY MANAGEMENT STRATEGY PROGRAM IN INCREASING STUDENTS READING INTERESR AT MTSN 3 SURABAYA CITYThe purpose of this study was to determine the literacy program management strategy in increasing students' interest in reading at MTsN 3 Surabaya City. This type of research uses qualitative descriptive research that collects data on the behavior and speech of a group of subjects. The research instruments used in this study were interviews, observations, and documentation for data collection. The results of the interviews revealed two strategies for literacy program management in increasing students' interest in reading at MTsN 3 Surabaya City: First, literacy program planning through a schedule. Second, teachers act as motivators, facilitators, and mentors for students. Management strategies in increasing students' interest in reading through student scientific writing and SAGU SAKU (One Teacher One Book). Challenges that can hinder the development of student literacy at MTsN 3 Surabaya City is the lack of experienced teachers using supporting learning media. Evaluation or assessment is very important in the learning process because it is used as a tool to measure students' abilities and interests in literacy activities.